Design trade‐off for a compact 5.8 GHz DSRC transponder front‐end. Issue 5 (May 2015) - Cidronali, Alessandro; Maddio, Stefano; Collodi, Giovanni; Manes, Gianfranco
ABSTRACT: This letter introduces a method for the optimum design of a compact transponder front‐end for dedicated short range communication (DSRC) operating at 5.8 GHz band and suitable for electronic toll collection (ETC) vehicular applications. The DSRC transponder front‐end is based on a circularly polarized antenna and a RF diode, which provides both the functionalities of envelope detector and back‐scatterer. The design method is based on the characterization and optimization of the frequency conversion mechanism occurring in the front‐end during up and downlink while the best trade‐off between design parameters are identified on the base of sensitivity and back‐scatterer gain. These parameters optimize the DSRC transponder front‐end in the two links and thus leads to the maximum operative range. The methods are validated through the design of three prototypes responding to different design constraints and tested in the context of a realistic scenario of DSRC for ETC according to the ETSI EN300674 communication layers. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:1187–1191, 2015